If x be an obtuse angle, y be an acute angle, and sin x = 2 sin ( x + 2 y ) , then choose the correct option.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Expanding the right hand side of the given equation and simplifying we get tan x = 1 − 2 cos ( 2 y ) 2 sin ( 2 y ) . Since x is obtuse, tan x < 0 . Since y is acute, sin ( 2 y ) > 0 . Therefore 1 − 2 cos ( 2 y ) < 0 , or cos ( 2 y ) > 2 1 or y < 6 π . This implies tan y < √ 3 1 < √ 2 1 . Since y is acute, therefore tan y > 0 , and hence 0 < tan y < √ 2 1 .
Problem Loading...
Note Loading...
Set Loading...
Since 9 0 ∘ < x < 1 8 0 ∘ , let x = 9 0 ∘ + θ , so that both 0 < θ , y < 9 0 ∘ . Then we have:
sin x sin ( 9 0 ∘ + θ ) sin ( 9 0 ∘ − θ ) cos θ 1 = 2 sin ( x + 2 y ) = 2 sin ( 9 0 ∘ + θ + 2 y ) = 2 sin ( 9 0 ∘ − θ − 2 y ) = 2 cos ( θ + 2 y ) = 2 cos θ cos 2 y − 2 sin θ sin 2 y = 2 cos 2 y − 2 tan θ sin 2 y Let x = 9 0 ∘ + θ As sin ( 1 8 0 ∘ − ϕ ) = sin ϕ and sin ( 9 0 ∘ − ϕ ) = cos ϕ
Using half-angle tangent substitution and let t = tan y .
1 + t 2 2 ( 1 − t 2 ) − 1 + t 2 4 t tan θ ⟹ 3 t 2 + 4 t tan θ − 1 ⟹ t = tan y = 1 = 0 = 3 4 tan 2 θ + 3 − 2 tan θ
Note that tan y decreases with θ monotonically. Therefore,
θ → 9 0 ∘ lim 3 4 tan 2 θ + 3 − 2 tan θ < 0 < tan y < θ → 0 ∘ lim 3 4 tan 2 θ + 3 − 2 tan θ tan y < 3 1
Hence 0 < tan y < 2 1 .